Effects of low lactose mare's milk yogurt consumption on gut microbiota function - Kozhakhmetov, Samat; Muhanbetganov, Nurislam; Pernebek, Zhanel; Babenko, Dmitriy; Tarzhanova, Dinar; Uyzbaeva, Indira; Khassenbekova, Zhanagul; Zhantureyeva, Akmaral; Jarmukhanov, Zharkyn; Kozhakhmetova, Saniya; Tultabayeva, Tamara; Kushugulova, Almagul (Functional Food Center, 2022)
Background: This study shows that the intake of low-lactose yogurt with the addition of mare's milk can affect the composition, biodiversity, and functional potential of the intestinal microflora.Purpose of the study: To study the effect of low-lactose drinking yogurt from a combination of mare's and cow's milk on the composition and functional repertoire of the fecal microbiota of rats.Methods: The study of the effect of low-lactose drinking yogurt from a combination of mare's and cow's milk on the intestinal microflora was carried out by dietary intervention for 4 weeks. Changes in the fecal microbiota were determined using V1-V3 sequencing of the hypervariable target region of the 16S rRNA gene. Functional prediction was carried out on the basis of the taxonomic structure of the amplicon sequence.Results: The results demonstrated a decrease in overall biodiversity both within the samples and between groups of animals. Discriminatory analysis revealed an increase in the relative content of Ruminococcaceae, Peptostreptococcaceae, indeterminate taxon at phylum level, Prevotellaceae and a decrease in Helicobacteraceae, Eubacteriumcoprostanoligenes group, Muribaculaceae, Lachnospiraceae, Lactobacillaceae. In addition, changes in the microbial structure also affected the predicted functional repertoire of the gut microbiota.Conclusion: These results demonstrate the consumption of low-lactose drinking yogurt from a combination of mare's and cow's milk, for a short time, can affect the composition and functional repertoire of the fecal microbiota. Keywords: Gut microbiome, rats, low-lactose yogurt, microbial diversity, functional repertoire.
Keywords: Gut microbiome; rats, low-lactose yogurt; microbial diversity; functional repertoire